Safety Management for the City Gas Industry Theory and Practice in China. - Xu, Peng (Cambridge Scholars Publishing, 2022)
As a high-quality energy source, city gas provides great convenience in our daily life and industries, but also poses dangers and accidents. Gas safety management covers many fields such as engineering, planning, design, construction, supervision, inspection, operation, maintenance and emergency response. It involves not only the employees in the industry, but also the billions of gas consumers.This book sorts out the important laws and regulations on safe production in force in China, and discusses the safety issues of city gas from a management perspective. Through various innovative feature.